Natural Killer Cell Inhibitory Receptor Expression in Humans and Mice: A Closer Look - Sternberg-Simon, Michal; Brodin, Petter; Pickman, Yishai; Önfelt, Björn; Kärre, Klas; Malmberg, Karl-Johan; Höglund, Petter; Mehr, Ramit (Frontiers in Immunology, 2013)
The Natural Killer (NK) cell population is composed of subsets of varying sizes expressing different combinations of inhibitory receptors for MHC class I molecules. Genes within the NK gene complex, including the inhibitory receptors themselves, seem to be the primary intrinsic regulators of inhibitory receptor expression, but the MHC class I background is an additional factor affecting the repertoire. In this paper, we have performed a parallel study of the inhibitory receptor repertoire in inbred mice of the C57Bl/6 background and in a cohort of 44 humans. Deviations of subset frequencies from the “product rule”, i.e. differences between observed and expected frequencies of NK cells, were used to identify MHC-independent and MHC-dependent control of receptor expression frequencies. Some deviations from the product rule were similar in mice and humans, such as the decreased presence of NK cell subset lacking inhibitory receptors. Others were different, including a role for NKG2A in determining over- or under-representation of specific subsets in humans but not in mice. Thus, while human and murine inhibitory receptor repertoires differed in details, there may also be shared principles governing NK cell repertoire formation in these two species.